Pengolahan Sampah Organik Melalui Penerapan Lubang Biopori Di RT 17 Pematang Gubernur - Septiani, Elnita; Daely, Putri Aprili; Sari, Dwi Mafika; Lestari, Ayu Tri; Bella, Ulvia; Putra, Iswidana Utama; Handayani, Tita; Putri, Yesi (Jurnal Dehasen Mengabdi, 2025)
Waste is always a major problem faced by every region. Poor waste management can cause losses, including foul odors, disruption of beauty, flooding, and the threat of increased various diseases. Biopori is an appropriate and environmentally friendly technology to address waste problems. Biopori can help reduce organic waste by decomposing it and turning it into compost that can be utilized by farmers. This activity aims to increase residents' understanding of the dangers of waste and the potential use of Biopori through outreach activities and practical demonstrations of Biopori installation in local residents' homes. The method of implementation of the activity was carried out through socialization to stimulate public interest and curiosity regarding Biopori Holes, as well as direct practice where students directly practiced making Biopori Holes. The result of your activity is the installation of one biopore hole as an example for the community to utilize and develop, as well as an increase in knowledge about the concept, benefits, and techniques of installing biopores, and how to manage waste, especially organic waste.